2020
DOI: 10.1080/09638288.2020.1742802
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of vestibular stimulation in cerebral palsy

Abstract: Identify the types and dosage of vestibular stimulation interventions in persons with cerebral palsy (CP), and establish the efficacy of these interventions on balance and function. Materials and Methods Thissystematic review followed Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols to search for studies evaluating vestibular stimulation interventions in persons with CP. Information sources included MEDLINE, Embase, CINAHL, Cochrane Central Register of Controlled Trials, clinicaltria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…A compromised motor skill makes it difficult for these children to perform dayto-day activities competently [7], including coordination, dexterity, balance, posture, gait, strength, speed, and agility [8]. However, it is a fact that these complications are not left unattended and have been addressed using numerous effective physical therapy techniques such as neurodevelopmental therapies [9], strength conditioning [10,11], balance and vestibular training [12], goal-directed motor learning [13], and virtual reality [14].…”
Section: Introductionmentioning
confidence: 99%
“…A compromised motor skill makes it difficult for these children to perform dayto-day activities competently [7], including coordination, dexterity, balance, posture, gait, strength, speed, and agility [8]. However, it is a fact that these complications are not left unattended and have been addressed using numerous effective physical therapy techniques such as neurodevelopmental therapies [9], strength conditioning [10,11], balance and vestibular training [12], goal-directed motor learning [13], and virtual reality [14].…”
Section: Introductionmentioning
confidence: 99%
“…Improvements in postural stability in children with CP have been demonstrated by stimulating the vestibular system via specific exercises [ 9 11 ]. However, a recent systematic review of the efficacy of vestibular stimulation in improving balance and function in people with CP highlighted contradictory results and methodological concerns in the underpinning literature [ 12 ]. All of the studies in the latter review evaluated vestibular stimulation in the form of exercise and movement: no studies were identified that evaluated electrical Vestibular Nerve Stimulation (VeNS) in CP.…”
Section: Introductionmentioning
confidence: 99%
“…VeNS is typically delivered via a headset that delivers electrical current via self-adhesive pads on the mastoid processes [ 19 ]. It can be conveniently delivered in the home environment [ 12 ], may be better tolerated than more traditional spinning and swinging exercises, and has the potential to impact on postural stability in children with CP.…”
Section: Introductionmentioning
confidence: 99%